AESTHETIC UNDERSTANDING AS A PERSONAL VIRTUE - Rakhmonova Makhfuza Kholmuradovna (Western European Studies, 2025)
In this article, the specifics of aesthetic taste and its role in aesthetic education of the person are analyzed
Keywords: aesthetic feeling; aesthetic taste; aesthetic consciousness